A wild boar dominated ungulate assemblage from an early Holocene natural pit fall trap: Cave shaft sediments in northwest England associated with the 9.3 ka BP cold event. (January 2016) - Lord, Tom C; Thorp, John A; Wilson, Peter
A highly unusual pit fall ungulate assemblage dominated by wild boar ( Sus scrofa ) was recovered during the recent exploration of a cave shaft in the upland karstic landscape of northwest England. Both the opening of the cave shaft to the surface and its infilling by clastic sediments are attributable to accelerated landscape erosion associated with the 9.3 ka BP climatic deterioration. Evidence that wild boar had died in winter or spring suggests that their deaths relate to the prolonged periods of annual snow cover experienced by the uplands of northwest England during the 9.3 ka BP event. The dominance of wild boar in the pit fall assemblage is explained by the snow pack concealing the open shaft and turning it into a baited trap for wild boar whenever it contained carrion. Wild boar bones splintered and chewed by wild boar demonstrate carrion cannibalism. Human presence is attested by slight butchery to an aurochs ( Bos primigenius ). How Mesolithic people adapted to climate change associated with the 9.3 ka BP event is a subject well worth pursuing.